Readaptarea profesională a persoanelor handicapate - Manea, Livius (Calitatea Vieții, 1993)
The concept of professional readapting takes a central place within the policies and programmes concerning the social protection of the handicapped and it refers to the assessment of professional skills, training and employment of them. The paper provides a perspective about the way in which this approach is conducted from the philantropic actions to the social security and the principles set up at the international level.